Setback and recovery AD 500-1500 - Foster, John, d. 1974 (London, UK SPCK, 1974)
Includes bibliographical references and index.
Keywords: Church history -- 6th century. -- study and teaching; Church history -- middle ages, 600-1500 -- study and teaching